Use of Semicircular Bending Test and Cohesive Zone Modeling to Evaluate Fracture Resistance of Stabilized Soils. Issue 1 (January 2017) - Zhang, Jun; Little, Dallas N.; Grajales, Javier; You, Taesun; Kim, Yong-Rak
The fracture resistance of a chemically stabilized base or subbase layer is important to the durability and sustainability of a pavement structure. Thus, an appropriate test protocol to characterize the fracture resistance of stabilized bases, subbases, and subgrade soils is essential to the design of pavement materials and structures. This paper proposes a protocol developed on the basis of the semicircular bending test to measure fracture resistance (i.e., fracture energy and fracture toughness) of chemically stabilized material. The effects of three test variables, including specimen thickness, notch length, and loading rate, on fracture properties were investigated, and appropriate values for these test variables were selected for the semicircular bending test protocol. The proposed semicircular bending test method was successful in characterizing the fracture resistance of three chemically stabilized materials. To address fracture properties of the chemically stabilized material more definitively, three-dimensional zone modeling was used and the simulations agreed very well with the experimental results. Both the fracture properties obtained from the experiment and the cohesive zone modeling indicated that polymer-stabilized limestone exhibited a much higher fracture resistance than cement-stabilized limestone and cement-stabilized sand. However, the polymer used demonstrated susceptibility to degradation in the presence of water. Correction of this limitation is the focus of ongoing research on this type of polymer.